Peranan Sistem Informasi Akuntansi Pendistribusian Barang Terhadap Pengendalian Persediaan Barang Jadi : Studi Kasus pada PT. Yudhistira Ghalia Indonesia - Muanas, Muanas; Hamdani, Riki (Jurnal Ilmiah Ranggagading (JIR), 2009)
This research was done to find out the role of information technology system used by publication company in managing ready made goods stock, partycurarly thatâs related to management components. Descriptive method was used here. The result of this research shows that computerized distribution system by MIS program in PT Yudhistira Ghalia Indonesia has given significant role in managing its ready made goods caused by computerized distribution system that help the company to find out deviation and to anticipate risk which is not impossible to happen. The report yielded, particuraly concerning ready made goods stoct, can be used by management to make printing plan and to find out manimum sum of ready made goods whit the result that the information of the ready made goods will be obtained more speedy and thereby the goal of the company can be achieved. Key words: Distribution system; Ready goods management